The Effect of Digital Advertising and Consumer Trust on Customer Loyalty through Customer Satisfaction: A Case Study of GladToGlow Products in Cirebon City - Sanjaya, Eka; Yusuf, (Journal Research of Social Science, Economics, and Management, 2026)
The development of digital marketing in Indonesia encourages local beauty brands to utilize digital advertising as a key strategy in building long-term relationships with consumers. Increasingly fierce competition requires companies to not only increase brand exposure, but also build customer trust and satisfaction to create sustainable customer loyalty. This study aims to analyze the influence of digital advertising and consumer trust on customer loyalty through customer satisfaction as a mediating variable in GladToGlow products in Cirebon City. This study used a quantitative approach with an associative method. Data was collected through an online questionnaire using Google Form on 120 respondents who were users of GladToGlow products at least once in the last six months, using purposive sampling techniques. Data analysis was carried out using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through the SmartPLS application. The results of the study show that digital advertising and consumer trust have a positive and significant effect on customer satisfaction and customer loyalty. In addition, customer satisfaction has been proven to play a role as a mediating variable that strengthens the influence of digital advertising and consumer trust on customer loyalty. An R-square value of 0.617 indicates that the model has moderate to strong explanatory abilities. These findings confirm the importance of the role of effective digital advertising and customer trust and satisfaction in building customer loyalty to local beauty brands.